The Role of Motivation and Anxiety on Error Awareness in Younger and Older Adults - Di Rosa, Elisa; Masina, Fabio; Vallesi, Antonino; Mapelli, Daniela (Frontiers in Psychiatry, 2021)
Healthy aging is associated with several changes not only in cognitive functions, but also in motivational and affective processes, which in turn interact with cognitive functions. The present study is aimed to investigate the interaction between reward motivation, anxiety and error awareness (EA), which is known to decline in healthy aging. Thirty healthy younger (age range: 19-35 years) and 30 healthy older adults (age range: 61-83 years) took part in the study. Every participant performed both the Classic Error Awareness Task (EAT) and a Motivational version of the EAT, in which motivational incentives were delivered after both correct responses and aware errors. For every participant, standardized measures of state and trait anxiety and cognitive functions were also collected. Results confirmed the presence of a significant age-related EA decline. However, there was neither an influence of reward motivation on EA, nor any relation between EA and anxiety. The use of online performance reward had indeed a detrimental influence on task performance, with both younger and older adults showing slower response times (RTs) during the Motivational EAT. An exploratory analysis suggested a possible relationship between state anxiety and the effect of rewards on RTs, since the more anxious participants were those showing the greater RT slowing during the Motivational EAT. Taken together, these findings show that reward motivation not always improves cognitive performance, and suggest future investigations on the possible interaction between anxiety, motivation and EA, also in clinical samples.